Enhancing Bio-Fertilization Potential of Introduced Hedysarum Species Through Indirect Root Inoculation: Implications for Agro-Ecological Sustainability in Arid Lands - Abdelhafid SEBIHI; Bakir MOUSSAOUALI; Baelhadj HAMDI-AÏSSA; Si Ammar KADI; Noureddine BOURAS (Studia Ecologiae et Bioethicae, 2024)
Saharan soils are devoid of Rhizobium bacteria specific to the Sulla plants which is indispensable for nitrogen fixation and soil fertility. The present study aims to test the possibility of formation nodules on the roots of some species of Hedysarum (Sulla) genus introduced in Ghardaïa region with indirect inoculation in the reason to optimize the use of nitrogen fertilizers. Three soil samples were chosen from three different districts of Algeria (Tizi-Ouzou, Sétif and El-Tarf) to be used as substrate and source of bacterial strains for three different species of Sulla (Hedysarum coronarium, Hedysarum carnosum, Hedysarum flexuosum). The results showed the formation of a considerable number of nodules in all treatments. The effect of species and samples of soils on the studied parameter was highly significant (p<0.000) at the 5% significance level. All cultivated species in the soil of Sétif could form significant more nodules compared to other soils. The disparity in the average number of nodules formed in the soil of Sétif represents a rate of 78.75% compared to the soil of Tizi-Ouzou. This study could contribute to improve fodder production of Sulla species cultivated in Ghardaïa region and also provides a forage rich in protein for local livestock.